Driver Responses to Simultaneous V2V and V2I Safety Critical Information in Left-turn Across Path Scenarios. (September 2015) - Richard, Christian; Divekar, Gautam; Philips, Brian H.; Bacon, L. Paige; Jerome, Christian
This paper describes two, part-task driving simulator studies that investigated how drivers handle safety information from multiple sources simultaneously, including in-vehicle and external sources. Specifically, the studies examined concurrent Driver-Infrastructure Interface (DII) and Driver-Vehicle Interface (DVI) displays for a gap-assist system while making a Left-Turn Across Path (LTAP) movement at a signalized intersection. Participants encountered repeated LTAP scenarios and indicated whether or not they would make a left turn through gaps in traffic that varied in size. Younger, middle, and older aged drivers participated in all experiments. The key factors examined included: gap size, age, display type (availability of DII and DVI information), and the visibility of oncoming traffic. The results indicated that participants primarily used the displays when their view of oncoming traffic was blocked, and they generally preferred the DII over the DVI. The key findings are discussed in terms of the effects of multiple sources of information, the effects of age, and visibility.